BEBEK SEBAGAI IDE PENCIPTAAN DALAM SENI GRAFIS - AFRI WARDI, Drs. Ariusmedi, M. Sn., Drs. Yusron Wikarya, M.Pd. (Universitas Negeri Padang, 2019)
This final work aims to visualize ducks in graphic art. If in human life, we know a lot of inspirational figures. But inspiration cannot always be learned from humans. In the world of fauna, there are many behaviors that we can take as wisdom in living life. For example animal life such as ducks. The author visualizes into graphic artwork. Aim to convey to the public that as intelligent human beings we can also learn from other beings, one of which is behavior in animals such as ducks.Keywords: Duck, Graphic.